Feeding Tolerance, Glucose Availability, and Whole-Body Total Carbohydrate and Fat Oxidation in Male Endurance and Ultra-Endurance Runners in Response to Prolonged Exercise, Consuming a Habitual Mixed Macronutrient Diet and Carbohydrate Feeding During Exercise - Rauch, Christopher E.; McCubbin, Alan J.; Gaskell, Stephanie K.; Costa, Ricardo J. S. (Frontiers in Physiology, 2022)
Using metadata from previously published research, this investigation sought to explore: 1) whole-body total carbohydrate and fat oxidation rates of endurance (e.g., half and full marathon) and ultra-endurance runners during an incremental exercise test to volitional exhaustion and steady-state exercise whilst consuming a mixed macronutrient diet and consuming carbohydrate during steady state running; and 2) feeding tolerance and glucose availability whilst consuming different carbohydrate regimes during steady state running. Competitively trained male endurance and ultra-endurance runners (n=28) consuming a balanced macronutrient diet (57±6% carbohydrate, 21±16% protein, 22±9% fat) performed an incremental exercise test to exhaustion, and one of three 3h steady-state running protocols involving a carbohydrate feeding regime (76-90g/h). Indirect calorimetry was used to determine maximum fat oxidation (MFO) in the incremental exercise, and carbohydrate and fat oxidation rates during steady-state running. Gastrointestinal symptoms (GIS), breath hydrogen (H2), and blood glucose responses were measured throughout the steady-state running protocols. Despite high variability between participants, high rates of MFO (mean (range): 0.66 (0.22-1.89) g/min), Fatmax (63 (40-94) % V̇O2max), and Fatmin (94 (77-100) % V̇O2max) were observed in the majority of participants in response to the incremental exercise test to volitional exhaustion. Whole-body total fat oxidation rate was 0.8 ± 0.3 g/min at the end of steady-state exercise, with 43% of participants presenting rates of ≥1.0g/min, despite the state of hyperglycaemia above resting homeostatic range (mean (95%CI): 6.9 (6.7-7.2) mmol/L). In response to the carbohydrate feeding interventions of 90g/h 2:1 glucose-fructose formulation, 38% of participants showed breath H2 responses indicative of carbohydrate malabsorption. Greater gastrointestinal symptom severity and feeding intolerance was observed with higher carbohydrate intakes (90g/h vs 76g/h) during steady state exercise, and was greatest when high exercise intensity was performed (i.e., performance test). Endurance and ultra-endurance runners can attain relatively high rates of whole-body fat oxidation during exercise in a post-prandial state and with carbohydrate provisions during exercise, despite consuming a mixed macronutrient diet. Higher carbohydrate intake during exercise may lead to greater gastrointestinal symptom severity and feeding intolerance.